The Treatment of ADHD in Adults: Efficacy and Safety of Stimulants and Non-Stimulants - Leszczyńska-Knaga, Elżbieta; Chodkowska, Ewa; Jakubczyk, Natalia; Dominiczak, Kinga; Szafrańska, Katarzyna; Mucha, Aleksandra; Graszka, Sylwia; Szeps, Aleksander; Dominiczak, Patrycja; Bielas, Kinga (Journal of Education, Health and Sport, 2025)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental condition with a complex etiology involving neurobiological, neuropsychological, and genetic factors. It is associated with brain structural and functional abnormalities, particularly in areas linked to executive functions, such as the prefrontal cortex and cerebellum. Disruptions in neurotransmission, particularly involving dopamine, norepinephrine, and serotonin, contribute to symptoms like impulsivity, hyperactivity, and inattention. Genetic studies reveal a strong hereditary basis, with variants related to dopaminergic and serotonergic systems. Although no single biomarker can definitively diagnose ADHD, a comprehensive diagnostic approach integrating clinical, neurophysiological, and neuroimaging data is necessary. Treatment strategies for ADHD in adults include pharmacological and non-pharmacological approaches. First-line medications are stimulants like methylphenidate and amphetamines, which improve attention and impulse control by increasing dopamine and norepinephrine levels. Non-stimulants, such as atomoxetine and guanfacine, are used when stimulants are contraindicated. While stimulants are more effective, non-stimulants may benefit patients with comorbid conditions. Treatment should be personalized, considering symptom severity, comorbidities, and treatment adherence. Neuroimaging shows that stimulants increase brain activity in areas related to cognitive control, while non-stimulants provide a more stable pharmacokinetic profile. A combined approach is essential for optimal ADHD management.